The Magnetoactive p-Ge Rod Waveguide Loss Analysis on the Concen-tration of Two Component Hole Charge Carriers - Nickelson, L.; Bubnelis, A.; Baskys, A.; Navickas, R. (Elektronika ir Elektrotechnika, 2011)
In this work are examined the phase and attenuation constants of open magnetoactive p-Ge rod waveguides. Our algorithm allows ana-lyzing the very high waveguide losses. Dispersion characteristics of p-Ge with two component hole charge carriers waveguide are calculated when the ratio of heavy holes’ concentration in the material is equal to 10%, 30% and 90% of the total free carrier concentration. Dispersion characteristics of the main helicon and eight higher helicon modes are presented here. There are the degeneration and the transformation of higher hybrid modes at some heavy holes’ concentrations. The waveguide broadbandwidth can be considerably extended due to the fact that the losses of the higher modes are considerably larger in comparisons to the main mode loss at the certain heavy holes’ concentration. Ill. 6, bibl. 12 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.286